2011
DOI: 10.1002/ajp.20991
|View full text |Cite
|
Sign up to set email alerts
|

Sex ratio affects sex‐specific innovation and learning in captive ruffed lemurs (Varecia variegataandVarecia rubra)

Abstract: Recent years have witnessed extensive research into problem solving and innovation in primates, yet lemurs have not been subjected to the same level of attention as apes and monkeys, and the social context in which novel behavior appears has rarely been considered. We gave novel foraging puzzlebox devices to seven groups of ruffed lemurs (Varecia variegata and Varecia rubra) to examine the factors affecting rates of innovation and social learning. We found, across a range of group sex ratios, that animals of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…One way forward may be to seek out research at locations that are home to several social groups of the same species (e.g., as is typical of primate sanctuaries or National Primate Research Centers). Lastly, although numbers may be small at a single institution, research in zoos where collaboration between institutions is often already in the culture may be a feasible route to obtaining data from several groups and species (e.g., Dean et al, 2011 ; Cronin, 2017 ). Researchers would need to consider variation introduced from multiple sites, but would likely increase their statistical power and the generalizability of their findings.…”
Section: Discussionmentioning
confidence: 99%
“…One way forward may be to seek out research at locations that are home to several social groups of the same species (e.g., as is typical of primate sanctuaries or National Primate Research Centers). Lastly, although numbers may be small at a single institution, research in zoos where collaboration between institutions is often already in the culture may be a feasible route to obtaining data from several groups and species (e.g., Dean et al, 2011 ; Cronin, 2017 ). Researchers would need to consider variation introduced from multiple sites, but would likely increase their statistical power and the generalizability of their findings.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, female and male subjects were equally likely to succeed in opening the boxes, i.e., to innovate, with a slight bias toward females. Previous studies on the acquisition of problem-solving techniques in lemurs showed that females were more likely to innovate (Kappeler 1987 ; Dean et al 2011 ; Schnoell and Fichtel 2012 ). A significant lack of a sex difference during innovation could be found in chimpanzees (Hrubesch et al 2009 ) and hyenas ( Crocuta crocuta : Benson-Amram and Holekamp 2012 ), but other studies in haplorrhine primates suggested a male bias (Reader and Laland 2001 ), indicating that sex alone is a weak predictor of innovativeness.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the likelihood/latency to contact each stimulus, we fitted a series of Cox proportional hazards models using the "survival" package (Therneau & Lumley, 2014). Survival models, such as Cox proportional hazards regression, are used in time-to-event data analyses (Jahn-Eimermacher, Lasarzik, & Raber, 2011) as they permit ceiling values to be included as censored data points in those cases where individuals did not approach a task (Dean et al, 2011). Given the opportunistic nature of our presentations, we were unable to standardise the distance at which either type of stimuli was presented.…”
Section: Likelihood/latency To Contact the Stimulusmentioning
confidence: 99%